Bacteriocinogenic LAB from cheeses - Application in biopreservation? - Favaro, Lorenzo; Barretto Penna, Ana Lucia [UNESP]; Todorov, Svetoslav Dimitrov [UNESP] (Elsevier B.V., 2015)
Over the last decade, there has been an explosion of basic and applied research on lactic acid bacteria bacteriocins, because of their potential as biopreservatives and inhibition of the growth of spoilage bacteria. Although bacteriocins can be produced during cheese production, their titers are much lower than those achieved in vitro fermentations under optimal physical and chemical conditions. Safety and technological traits of the bacteriocinogenic lactic acid bacteria (LAB) have to be considered before their wide-spread applications. This review described the perspectives and hurdles to be solved in order to definitively disclose the potential of bacteriocins in the production of safe and healthy cheese commodities.